Bioinspired strategies for stretchable conductors - Zhang, Feilong (2023)
Stretchable conductors are indispensable components of stretchable electronic devices, such as stretchable sensors, transistors, light-emitting diode arrays, solar cells, and so on. However, most of the conductive materials are stiff with very low stretchability. Nature has evolved various strategies to realize stretchability, which give a lot of inspirations to the design and fabrication of stretchable conductors. We herein summarized the nature’s strategies to realize stretchability and revealed the underlying mechanisms. After that, the applications of these strategies in fabricating stretchable conductors are exemplified and the effects of some important parameters on the performances are discussed. Then, possible applications of these stretchable conductors are summarized. Finally, critical issues in the stretchable conductors are discussed and several prospective exploration directions are provided. [Figure not available: see fulltext.]